Peran Maulana Hasanudin dalam Membangun Kekuatan Bisnis Internasional dan Jaringan Perdagangan Global di Banten - Ira Juhairannisa; Munawaroh Munawaroh (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Maulana Hasanuddin, the founder of the Banten Sultanate, played a pivotal role in establishing international business strength and global trade networks in the 16th century. Through his strategic policies, he transformed Banten into a maritime trade hub connecting Southeast Asia, the Middle East, and Europe. Capitalizing on its strategic location in the Sunda Strait, Maulana Hasanuddin developed the Port of Banten into a crucial node for the spice trade. He fostered trade alliances with various parties, including foreign merchants, and strengthened diplomatic relations through Islamic cultural and religious approaches. This role not only bolstered the local economy but also positioned Banten as a significant power in the global trade network. This study examines Maulana Hasanuddin's role in the economic and maritime political context and its impact on the development of international trade during the period.